Primary extradural meningioma presenting as a neck mass: Case report and review of the literature. Issue 8 (16th June 2015) - Saade, Rami; Hessel, Amy; Ginsberg, Lawrence; Fuller, Greg; Bell, Diana; Irish, Jonathan
Abstract Background Primary extradural meningiomas (PEMs) are rare, particularly those involving the paraspinal cervical area, so little is known about them. We identified a new case and compared it with 10 previous cases, addressed the diagnostic challenges, and highlighted the clinical and pathologic characteristics. Methods We conducted a case report and literature review of PEM cases reported since 1976. Results A 59‐year‐old man presented with right neck stiffness and discomfort that was present over the last several months, which is consistent with other cases. CT scan and MRI revealed a paraspinal cervical mass. Fine‐needle aspiration (FNA) and core biopsy revealed spindle cells with whorling consistent with meningioma. The patient underwent complete en bloc resection of the tumor. The PEM was histologically benign. Conclusion Cervical PEMs should be considered in the differential diagnosis of a deep neck mass. These tumors are typically benign and are surgically resected. © 2014 Wiley Periodicals, Inc. Head Neck37: E92–E95, 2015